Upgrading The L Word: Generation Q - Rutherford, A; Baker, S (Media/Culture, 2020)
The L Word: Generation Q is the reboot of The L Word, a long running series about a group of lesbians and bisexuals in Los Angeles in the early 2000s. Both programmes are unique in their positioning of lesbian characters and have been well received by audiences and critics alike. These programmes present a range of characters and narratives, previously excluded from mainstream film and television, bringing a refreshing change from the destructive images typically presented before. We argue that the reboot Generation Q now offers more meaningful representation of the broader lesbian and transgender communities, and discuss its relevance in the changing portrayals of gay representation. Gay visibility has never really been an issue in the movies. Gays have always been visible. It is how they have been visible that has remained offensive for almost a century. (Russo 66) In 2004 The L Word broke new ground as the very first television series written and directed by predominantly queer women. This set it apart from previous representations of lesbians by Hollywood because it portrayed a community rather than an isolated or lone lesbian character, that was extraneous to a cast of heterosexuals (Moore and Schilt). The series brought change, and where Hollywood was more often “reluctant to openly and non-stereotypically engage with gay subjects and gay characters” (Baker 41), the L Word offered an alternative to the norm in media representation. “The L Word’s significance lies in its very existence” according to Chambers (83), and this article serves to consider this significance in conjunction with its 2019 reboot, the L Word: Generation Q, to ascertain if the enhanced visibility and gay representation influences the system of representation that has predominantly been excluding and misrepresentative of gay life. The exclusion of authentic representation of lesbians and gays in Hollywood film is not new. Over time, however, there has been an increased representation of gay characters in film and television. However, beneath the positive veneer remains a morally disapproving undertone (Yang), where lesbians and gays are displayed as the showpiece of the abnormal (Gross, "Out of the Mainstream"). Gross ("Out of the Mainstream") suggests that through the ‘othering’ of lesbians and gays within media, a means of maintaining the moral order is achieved, and where being ‘straight’ results in a happy ending. Lesbians and gays in film thus achieve what Gerbner referred to as symbolic annihilation, purposefully created in a bid to maintain the social inequity. This form of exclusion often saw controversial gay representation, with a history of portraying these characters in a false, excluding, and pejorative way (Russo; Gross, "What Is Wrong"; Hart). The history of gay representation in media had at times been monstrous, playing out the themes of gay sexuality as threatening to heterosexual persons and communities (Juárez). Gay people were incorrectly stereotyped, and gay lives were seen through the slimmest of windows. Walters (15) argued that it was “too often” that film and television images would narrowly portray gays “as either desexualized or over sexualized”, framing their sexuality as the sole identity of the character. She also contested that gay characters were “shown as nonthreatening and campy 'others' or equally comforting and familiar boys (and they are usually boys, not girls) next door” (Walters 15). In Russo’s seminal text, The Celluloid Closet, he demonstrated that gay characters were largely excluded from genuine and thoughtful presentation in film, while the only option given to them was how they died. Gay activists and film makers in the 1980s and beyond built on the momentum of AIDS activism (Streitmatter) to bring films that dealt with gay subject matter more fairly than before, with examples like The Birdcage, Philadelphia, To Wong Foo, Thanks for Everything! Julie Newmar, and In and Out. Walters argues that while “mainstream films like Brokeback Mountain and The Kids are Alright entertain moviegoers with their forthright gay themes and scenes” (12), often the roles have been more of tokenisation, representing the “surprisingly gay characters in a tedious romcom, the coyly queer older man in a star-studded indie hit, the incidentally gay sister of the lead in a serious drama” (Walters 12). This ambivalence towards the gay role model in the media has had real world effects on those who identify themselves as lesbian or gay, creating feelings of self-hatred or of being ‘unacceptable’ citizens of society (Gamson), as media content “is an active component in the cultural process of shaping LGBT identities” (Sarkissian 147). The stigmatisation of gays was further identified by the respondents to a study on media and gay identity, where “the prevailing sentiment in these discussions was a sense of being excluded from traditional society” (Gomillion and Guiliano 343). Exclusion promotes segregation and isolation, and since television media are ever-present via conventional and web-based platforms, their messages are increasingly visible and powerful. The improved portrayal of gay characters was not just confined to the area of film and television however, and many publications produced major stories on bi-sexual chic, lesbian chic, the rise of gay political power and gay families. This process of greater inclusion, however, has not been linear, and in 2013 the media advocacy group known as the Gay and Lesbian Alliance against Defamation (GLAAD) mapped the quantity, quality, and diversity of LGBT people depicted in films, finding that there was still much work to be done to fairly include gay characters (GLAAD Studio Responsibility Index). In another report made in 2019, which examined cable and streaming media, GLAAD found that of the 879 regular characters expected to appear on broadcast scripted primetime programming, 10.2% were identified as gay, lesbian, bisexual, transgender and or queer (GLAAD Where Are We on TV). This was the highest number of queer characters recorded since the start of their reporting. In January 2004, Showtime launched The L Word, the first scripted cable television to focus chiefly on lesbians. Over the course of six seasons it explored the deep bonds that linked the members of an evolving lesbian friendship circle. The central themes of the programme were the love and friendship between the women, and it was a television programme structured by its own values and ideologies. The series offered a moral argument against the widespread sexism and anti-gay prejudice that was evident in media. The cast, however, were conventionally beautiful, gender normative, and expensively attired, leading to fears that the programme would appeal more to straight men, and that the sex in the programme would be exploitative and pornographic. The result, however, was that women’s sex and connection were foregrounded, and appeared as a central theme of the drama. This was, however, ground-breaking television. The showrunner of the original L Word, Ilene Chaiken, was aware of the often-damning account of lesbians in Hollywood, and the programme managed to convey an indictment of Hollywood (Mcfadden). The L Word increased lesbian visibility on television and was revolutionary in countering some of the exclusionary and damaging representation that had taken place before. It portrayed variations of lesbians, showing new positive representations in the form of power lesbians, sports lesbians, singles, and couples. Broadly speaking, gay visibility and representation can be marked and measured by levels of their exclusion and inclusion. Sedgwick said that the L Word was particularly important as it created a “lesbian ecology—a visible world in which lesbians exist, go on existing, exist in forms beyond the solitary and the couple, sustain and develop relations among themselves of difference and commonality” (xix). However, as much as this programme challenged the previous representations it also enacted a “Faustian bargain because television is a genre which ultimately caters to the desires and expectations of mainstream audiences” (Wolfe and Roripaugh 76). The producers knew it was difficult to change the problematic and biased representation of queer women within the structures of commercial media and understood the history of queer representation and its effects. Therefore, they had to navigate between the legitimate desire to represent lesbians as well as being able to attract a large enough mainstream audience to keep the show commercially viable. The L Word: Generation Q is the reboot of the popular series, and includes some of the old cast, who have also become the executive producers. These characters include Bette Porter, who in 2019 is running for the office of the Mayor of Los Angeles. Shane McCutchen returns as the fast-talking womanising hairdresser, and Alice Pieszecki in this iteration is a talk show host. When interviewed, Jennifer Beals (executive producer and Bette Porter actor) said that the programme is important, because there have been no new lesbian dramas to follow after the 2004 series ended (Beals, You Tube). Furthermore, the returning cast members believe the reboot is important because of the increased attacks that queer people have been experiencing since the election of Donald Trump in 2016. Between the two productions there have been changes in the film and television landscape, with additional queer programmes such as Pose, Orange Is the New Black, Euphoria, RuPaul’s Drag Race, and Are You the One, for example. The new L Word, therefore, needed to project a new and modern voice that would reflect contemporary lesbian life. There was also a strong desire to rectify criticism of the former show, by presenting an increased variation of characters in the 2019 series. Ironically, while the L Word had purposefully aimed to remove the negativity of exclusion through the portrayal of a group of lesbians in a more true-to-life account, the limited character tropes inadvertently marginalised other areas of lesbian and queer representation. These excluded characters were for example fully representative trans characters. The 2000s television industry had seemingly returned to a period of little interest in women’s stories generally, and though queer stories seeped into popular culture, there was no dedicated drama with a significant focus on lesbian story lines (Vanity Fair). The first iteration of The L Word was aimed at satisfying lesbian audiences as well as creating mainstream television success. It was not a tacky or pornographic television series playing to male voyeuristic ideals, although some critics believed that it included female-to-female sex scenes to draw in an additional male viewership (Anderson-Minshall; Graham). There was also a great emphasis on processing the concept of being queer. However, in the reboot Generation Q, the decision was made by the showrunner Marja-Lewis Ryan that the series would not be about any forms of ‘coming out stories’, and the characters were simply going about their lives as opposed to the burdensome tropes of transitioning or coming out. This is a significant change from many of the gay storylines in the 1990s that were seemingly all focussed on these themes. The new programme features a wider demographic, too, with younger characters who are comfortable with who they are. Essentially, the importance of the 2019 series is to portray healthy, varied representations of lesbian life, and to encourage accurate inclusion into film and television without the skewed or distorted earlier narratives. The L Word and L Word: Generation Q then carried the additional burden of countering criticisms The L Word received. Roseneil explains that creating both normalcy and belonging for lesbians and gays brings “cultural value and normativity” (218) and removes the psychosocial barriers that cause alienation or segregation. This “accept us” agenda appears through both popular culture and “in the broader national discourse on rights and belongings” (Walters 11), and is thus important because “representations of happy, healthy, well integrated lesbian and gay characters in film or television would create the impression that, in a social, economic, and legal sense, all is well for lesbians and gay men” (Schacter 729). Essentially, these programmes shouldered the burden of representation for the lesbian community, which was a heavy expectation. Critiques of the original L Word focussed on how the original cast looked as if they had all walked out of a high-end salon, for example, but in L Word: Generation Q this has been altered to have a much more DIY look. One of the younger cast members, Finlay, looks like someone cut her hair in the kitchen while others have styles that resemble YouTube tutorials and queer internet celebrities (Vanity Fair). The recognisable stereotypes that were both including and excluding have also altered the representation of the trans characters. Bette Porter’s campaign manager, for example, determines his style through his transition story, unlike Max, the prominent trans character from the first series. The trans characters of 2019 are comfortable in their own skins and supported by the community around them. Another important distinction between the representation of the old and new cast is around their material wealth. The returning cast members have comfortable lives and demonstrate affluence while the younger cast are less comfortable, expressing far more financial anxiety. This may indeed make a storyline that is closer to heterosexual communities. The L Word demonstrated a sophisticated awareness of feminist debates about the visual representation of women and made those debates a critical theme of the programme, and these themes have been expanded further in The L Word: Generation Q. One of the crucial areas that the programme/s have improved upon is to denaturalise the hegemonic straight gaze, drawing attention to the ways, conventions and techniques of reproduction that create sexist, heterosexist, and homophobic ideologies (McFadden). This was achieved through a predominantly female, lesbian cast that dealt with stories amongst their own friend group and relationships, serving to upend the audience position, and encouraging an alternative gaze, a gaze that could be occupied by anyone watching, but positioned the audience as lesbian. In concluding, The L Word in its original iteration set out to create something unique in its representation of lesbians. However, in its mission to create something new, it was also seen as problematic in its representation and in some ways excluding of certain gay and lesbian people. The L Word: Generation Q has therefore focussed on more diversity within a minority group, bringing normality and a sense of ‘realness’ to the previously skewed narratives seen in the media. In so doing, “perhaps these images will induce or confirm” to audiences that “lesbians and gay men are already ‘equal’—accepted, integrated, part of the mainstream” (Schacter 729). References Anderson-Minshall, Diane. “Sex and the Clittie, in Reading the L Word: Outing Contemporary Television.”  Reading Desperate Housewives. Eds. Janet McCabe and Kim Akass. I.B. Tauris, 2006. 11–14. Are You the One? Presented by Ryan Devlin. Reality television programme. Viacom Media Networks, 2014. Baker, Sarah. “The Changing Face of Gay Representation in Hollywood Films from the 1990s Onwards: What’s Really Changed in the Hollywood Representation of Gay Characters?” The International Journal of Interdisciplinary Cultural Studies 10.4 (2015): 41–51. Brokeback Mountain. Dir. Ang Lee. Film. Focus Features, 2005. Chambers, Samuel. A. “Heteronormativity and The L Word: From a Politics of Representation to a Politics of Norms.” Reading Desperate Housewives. Eds. Janet McCabe and Kim Akass. I.B. Tauris, 2006. 81–98. Euphoria. Dir. Sam Levinson. Television Series. HBO, 2019.  Gamson, Joshua.  “Sweating in the Spotlight: Lesbian, Gay and Queer Encounters with Media and Popular Culture.” Handbook of Lesbian and Gay Studies.London: Sage, 2002. 339–354. Graham, Paula. “The L Word Under-whelms the UK?” Reading Desperate Housewives. Eds. Janet McCabe and Kim Akass. I.B. Tauris, 2006. 15–26.  Gross, Larry. “What Is Wrong with this Picture? Lesbian Women and Gay Men on Television.” Queer Words, Queer Images: Communication and the Construction of Homosexuality. Ed. R.J. Ringer. New York: New York UP, 1994. 143–156. Gross, Larry. “Out of the Mainstream: Sexual Minorities and the Mass Media.” Gay People, Sex, and the Media. Eds. M. Wolf and A. Kielwasser. Haworth Press, 1991. 19–36.  Hart, Kylo-Patrick. R. “Representing Gay Men on American Television.” Journal of Men’s Studies 9 (2000): 59–79. In and Out. Dir. Frank Oz. Film. Paramount Pictures, 1997. Juárez, Sergio Fernando. “Creeper Bogeyman: Cultural Narratives of Gay as Monstrous.” At the Interface / Probing the Boundaries 91 (2018): 226–249. McFadden, Margaret. T. The L Word. Wayne State University Press, 2014. Moore, Candace, and Kristin Schilt. “Is She Man Enough? Female Masculinities on The L Word.” Reading Desperate Housewives. Eds. Janet McCabe and Kim Akass. I.B. Tauris, 2006. 159–172. Orange Is the New Black. Dir. Jenji Johan. Web series. Netflix Streaming Services, 2003–. Philadelphia. Directed by Jonathan Demme. Film. Tristar Pictures, 1993. Pose. Dirs. Ryan Murphy, Steven Canals, and Brad Falchuk. Television series. Color Force, 2018.  Roseneil, Sasha. “On Missed Encounters: Psychoanalysis, Queer Theory, and the Psychosocial Dynamics of Exclusion.” Studies in Gender and Sexuality 20.4 (2019): 214–219. RuPaul’s Drag Race. Directed by Nick Murray. Reality competition. Passion Distribution, 2009–. Russo, Vito. The Celluloid Closet. Rev. ed. New York: Harper & Row, 1987. Sarkissian, Raffi. “Queering TV Conventions: LGBT Teen Narratives on Glee.” Queer Youth and Media Cultures. Ed. C. Pullen. Palgrave Macmillan, 2014. 145–157. Sedgwick, Eve Kosofsky. “Foreword: The Letter L.” Reading 'The L Word’: Outing Contemporary Television. Reading Desperate Housewives. Eds. Janet McCabe and Kim Akass. I.B. Tauris, 2006. 20–25. Schacter, Jane S. “Skepticism, Culture and the Gay Civil Rights Debate in Post-Civil-Rights Era.” Harvard Law Review 110 (1997): 684–731. Streitmatter, Rodger. Perverts to Fab Five: The Media’s Changing Depiction of Gay Men and Lesbians. New York: Routledge. 2009. The Birdcage. Dir. Mike Nichols. Film. United Artists, 1995. The Kids Are Alright. Dir. Lisa Cholodenko. Film. Focus Features, 2010. The L Word. Created by Ilene Chaiken, Kathy Greenberg, and Michelle Abbott. TV drama. Showtime Networks, 2004–2009.  The L Word: Generation Q. Prods. Ilene Chaiken, Jennifer Beals, Katherine Moennig, and Leisha Hailey. TV drama. Showtime Networks, 2019–. To Wong Foo, Thanks for Everything! Julie Newmar. Dir. Beeban Kidron. Film. Universal Pictures, 1995. Walters, Suzanna Danuta. The Tolerance Trap: How God, Genes and Good Intentions Are Sabotaging Gay Equality. New York: New York UP, 2014. Yang, Alan. "From Wrongs to Rights: Public Opinion on Gay and Lesbian Americans Moves towards Equality." New York: The Policy Institute of the National Gay and Lesbian Task Force, 1999.